2003
DOI: 10.1074/jbc.m301991200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Intersubunit Interactions between S4 and S5 Transmembrane Segments of the Shaker Potassium Channel

Abstract: Voltage-gated potassium channels are transmembrane proteins made up of four subunits, each comprising six transmembrane (S1-S6) segments. S1-S4 form the voltage-sensing domain and S5-S6 the pore domain with its central pore. The sensor domain detects membrane depolarization and transmits the signal to the activation gates situated in the pore domain, thereby leading to channel opening. An understanding of the mechanism by which the sensor communicates the signal to the pore requires knowledge of the structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
6
31
2
Order By: Relevance
“…The proximity of two cysteine side chains was also determined by tight binding of externally applied Cd 2ϩ ions, resulting in inhibition of channel function. The functional consequences of both CuPhe-induced cross-linking and Cd 2ϩ coordination have previously been used to infer distances between pairs of cysteine side chains of Ͻ10 Å in other channel types (31)(32)(33)(34)(35). Furthermore, both CuPhe-induced cysteine cross-linking (18,19) and Cd 2ϩ inhibition of single cysteine mutants (23) have been investigated in the CFTR channel pore using electrophysiological recording.…”
Section: Methodsmentioning
confidence: 99%
“…The proximity of two cysteine side chains was also determined by tight binding of externally applied Cd 2ϩ ions, resulting in inhibition of channel function. The functional consequences of both CuPhe-induced cross-linking and Cd 2ϩ coordination have previously been used to infer distances between pairs of cysteine side chains of Ͻ10 Å in other channel types (31)(32)(33)(34)(35). Furthermore, both CuPhe-induced cysteine cross-linking (18,19) and Cd 2ϩ inhibition of single cysteine mutants (23) have been investigated in the CFTR channel pore using electrophysiological recording.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments where nonspecific leaks developed during the experiment were simply discarded. The reversibility of covalent bonds was tested with 5 mM BMS (bis(2-mercaptoethylsulfone)) (Calbiochem, San Diego, CA) a water-soluble reagent considered to be a superior reducing agent than dithiothreitol (25,26). The percentage of currents remaining after MTS modification was computed at V m ϭ Ϫ150 mV using [(I wash )/(I ctrl )] ϫ 100 where I wash is the whole cell peak current remaining after MTS application and washout and I ctrl is the whole cell peak current measured before MTS application.…”
Section: Methodsmentioning
confidence: 99%
“…In subsequent studies based on disulfide linkage between S4 and S5 the VSD of one subunit was shown to make close contact with the pore domain of a neighbouring subunit, not with its own subunit [60,[71][72][73][74]. This proposed interaction between two neighbouring subunits was later on supported by the X-ray structure of Kv1.2 [37].…”
Section: The Vsd Connects To the Upper End Of S5 In A Neighbouring Pomentioning
confidence: 61%